The Effects of Insole-Based Visual Feedback on Weight-Bearing in Patients Undergoing Total Hip Replacement - Marin, Luca; Vandoni, Matteo; Zaza, Giancarlo; Febbi, Massimiliano; Pedrotti, Luisella; Chiodaroli, Matteo; Lovecchio, Nicola; Manzoni, Federica (International journal of environmental research and public health, 2021)
This study aimed to investigate the visual biofeedback effect of a sensorized system for plantar pressure dynamic evaluation of in patients with a total hip replacement. Experimental group followed the rehabilitation training wearing sensorized insoles that provided images on three monitors. The control group followed the verbal instructions of physiotherapists during training. Weight bearing percentage healthy limb (WBPH), weight bearing percentage surgical limb (WBPS), swing healthy limb (SWH) and swing surgical limb (SWS) improved significantly more in the experimental group. The results underline the effectiveness of visual biofeedback based on sensorized system with dynamic evaluation of the plantar pressure.
Keywords: obuv; Feedback, Sensory; náhrada kyčelního kloubu; senzorická zpětná vazba; zatížení muskuloskeletálního systému; lidé; Arthroplasty, Replacement, Hip; biofeedback (psychologie); Shoes; Biofeedback, Psychology; Weight-Bearing; Humans